Development and Validation of a Reverse Phase HPLC Method for the Analysis of Isradipine in Pharmaceutical Dosage Forms - Nageswara Rao, R.; Nagaraju, P.; Srinivasulu, C.; Radha Krishnamurthy, P.; Sireesha, D.; Sumanth Reddy, V. (Asian Journal of Chemistry, 2016)
A rapid and sensitive high performance liquid chromatographic method was developed for the estimation of isradipine in pharmaceutical dosage forms. Isradipine was chromatographed on a reverse phase C18 column in a mobile phase consisting of methanol : water in the ratio of 70 : 30 v/v. The mobile phase was pumped at flow rate of 1 mL/min and the eluents were monitored at 290 nm. The calibration curve was linear in the range of 1 – 100 μg/mL. The intra- and inter-day variation was found to be less than 2% showing high precision of the assay method. The mean recovery of the drug from the solution containing 20 μg/mL was 999.75 ± 1.10% indicating high accuracy of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy the proposed HPLC method may be used for determining isradipine in bulk drug samples and pharmaceutical dosage forms.